Dynamics of Threading Intercalation: Effects of DNA Supercoiling and Drug Size - Jansson, Erik T. (My University, 2007)
Binuclear ruthenium(II) complexes with a bidppz bridging ligand are known to display kinetic and thermodynamic selectivity for AT-rich DNA sequences, since their intercalation require local melting of the DNA helix, in order to thread through the DNA base-pair stack. In the present study the threading activation energies in AT-DNA are found to increase with the size of the ancillary ligands for complexes in the ΔΔ-configuration. It is known for proteins, that in addition to sequence selectivity, there are many topological recognition patterns in DNA targeting. Hence, it is interesting to study if such selectivity exists also for binuclear ruthenium(II) complexes. Here, the effect of DNA supercoils on threading intercalation is investigatedwith spectroscopicmethods, such as circular and linear dichroism, and fluorescence spectroscopy. The present work show supercoiled plasmid DNA, in comparison to linear, to enhance the initial threading intercalation rate by two orders of magnitude. Further, in contrast to what is observed for linear DNA, the intercalation into supercoiled DNA is clearly biphasic, where the second phase is considerably slower. This can be explained as a result of unwinding of the supercoiled DNA closer to its relaxed state during intercalation, where the threading intercalation rate is promoted in the early phase by the free energy stored in the negatively supercoiled plasmid. In the later phase, binding is slowed as unwinding decreases the free energy available, increasing the energy threshold for intercalation.
Keywords: Kemi; Biofysikalisk kemi; Kinetik; Spektroskopi; Chemical Sciences; Biophysical chemistry; Kinetics; Spectroscopy